Greater symptom burden results in reduced exercise tolerance in adolescents following concussion. (23rd February 2022) - Fyffe, Andrew; Carron, Michael A.; Orr, Rhonda; Cassimatis, Maree; Browne, Gary
ABSTRACT: Objectives: To explore the relationship between symptoms and exercise tolerance in adolescents following concussion. Methods: A retrospective analysis of 417 adolescents who attended a concussion service between January 2015 and April 2021 was performed, with 149 meeting eligibility criteria for inclusion. Post-Concussion Symptom Scale (PCSS) and graded exercise tolerance time (min) were assessed at initial and follow-up visits. Spearman's correlation was used to examine the relationship between PCSS scores and exercise time. Results: Adolescents (n = 149, 13.9 ± 1.7 years, 66.4% male) presented at 28.6 ± 19.7 days post-injury. Statistically significant correlations were identified between initial (r = −0.36, p < .001) and follow-up (r = −0.41, p < .001) PCSS scores and exercise time among all participants. Initial PCSS and initial exercise time were inversely correlated for males (r = −0.24, p = .018) and females (r = −0.22, p = .127). Follow-up PCSS and follow-up exercise time were inversely correlated for males (r = −0.30, p = .003) and females (r = −0.35, p = .014). Conclusion: There is a statistically significant relationship between higher PCSS and poorer exercise time and both factors should be considered together to provide the most accurate assessment, particularly in females.